2023
DOI: 10.3390/plants12102027
|View full text |Cite
|
Sign up to set email alerts
|

Achyrocline satureioides Hydroalcoholic Extract as a Hypoallergenic Antimicrobial Substitute of Natural Origin for Commonly Used Preservatives in Cosmetic Emulsions

Abstract: Achyrocline satureioides is a South American herb used in traditional medicine to treat a wide range of ailments. The healing and antimicrobial effects of this plant have already been covered by many studies, which have confirmed its beneficial effects on human health. In this study, the antimicrobial effect of A. satureioides hydroalcoholic extract against Escherichia coli ATCC10536, Staphylococcus aureus ATCC25923, Staphylococcus epidermidis ATCC12228 and Lactobacillus acidophilus INCQS00076 was determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Natural extracts possess antibacterial properties and have the potential to replace preservatives in cosmetics while maintaining safety. Langová et al (2023) [8] suggested that the hydroalcoholic extract of Achyrocline satureioides could be a natural and hypoallergenic alternative, with antimicrobial properties, for commonly used preservatives in cosmetic emulsions. The fruits of the large cranberry (Vaccinium macrocarpon Aiton) are a valuable source of biologically active compounds, such as anthocyanins, phenolic compounds, flavonols, et al [9].…”
mentioning
confidence: 99%
“…Natural extracts possess antibacterial properties and have the potential to replace preservatives in cosmetics while maintaining safety. Langová et al (2023) [8] suggested that the hydroalcoholic extract of Achyrocline satureioides could be a natural and hypoallergenic alternative, with antimicrobial properties, for commonly used preservatives in cosmetic emulsions. The fruits of the large cranberry (Vaccinium macrocarpon Aiton) are a valuable source of biologically active compounds, such as anthocyanins, phenolic compounds, flavonols, et al [9].…”
mentioning
confidence: 99%